On a planetary forcing of global seismicity - Stéphanie Dumont; Jean de Bremond d’Ars; Jean-Baptiste Boulé; Vincent Courtillot; Marc Gèze; Dominique Gibert; Vladimir Kossobokov; Jean-Louis Le Mouël; Fernando Lopes; Maria C. Neves; Graça Silveira; Graça Silveira; et al. (Frontiers in Earth Science)
We have explored the temporal variability of the seismicity at global scale over the last 124 years, as well as its potential drivers. To achieve this, we constructed and analyzed an averaged global seismicity curve for earthquakes of magnitude equal or greater than 6.0 since 1900. Using Singular Spectrum Analysis, we decomposed this curve and compared the extracted pseudo-cycles with two global geophysical parameters associated with Earth’s tides: length-of-day variations and sea-level changes. Our results reveal that these three geophysical signal curves can be reconstructed up to ∼90% by the sum of up to seven periodic components ranging from 1 to ∼60 years, largely aligned with planetary ephemerides. We discuss these results in the framework of Laplace’s theory, with a particular focus on the phase relationships between seismicity, length-of-day variations, and sea-level changes to further elucidate the underlying physical mechanisms. Finally, integrating observations from seismogenic regions, we propose a possible trigger mechanism based on solid Earth–hydrosphere interactions, emphasizing the key role of water-rock interactions in modulating earthquake occurrence.